Waste Analysis in the Power Change Process to Reduce Waste Using the Lean Service Method: Analisis Pemborosan pada Proses Perubahan Daya Untuk Mengurangi Pemborosan dengan Metode Lean Service - Ahmad, Dzaki Syahriar; Aryanny, Enny (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Service inefficiencies in utility companies can significantly hinder customer satisfaction and operational effectiveness. Specific Background: At PT XYZ, the power-change service process for Medium Voltage (MV) customers has faced persistent delays and procedural complications. Knowledge Gap: While Lean methodologies have been applied in manufacturing, limited research exists on their implementation within utility service workflows, particularly for MV customer segments. Aims: This study aims to analyze and minimize Waste within PT XYZ’s MV power-change service using the Lean Service approach. Results: Utilizing Process Activity Mapping (PAM) and Value Stream Mapping (VSM), five major Waste types were identified: document delays (W3), miscommunication (UC2), incorrect materials (II1), material delays (W2), and bureaucratic procedures (L1). Root Cause Analysis with Fishbone Diagrams informed targeted interventions, such as digital forms, visual SOPs, and Just-in-Time material management. These measures raised Process Cycle Efficiency (PCE) from 49.2% to 60.7%, and shortened lead time by 8,160 minutes. Novelty: The integration of PAM and Lean VSM in a utility service context, with tailored communication and digital solutions, represents a novel adaptation of industrial Lean tools. Implications: Findings demonstrate the applicability of Lean Service tools in complex service environments, offering actionable insights for utility firms aiming to enhance performance and customer experience. Highlights: Identifies key service inefficiencies using Lean tools. Achieves significant gains in efficiency and lead-time. Introduces tailored digital and visual process improvements. Keywords: Lean Service, Process Efficiency, Value Stream Mapping, Waste Reduction, Utility Services